2015
DOI: 10.14744/nci.2014.96967
|View full text |Cite
|
Sign up to set email alerts
|

Aural myiasis: case report

Abstract: Myiasis is the infestation of live vertebrates with dipterous larvae. Aural myiasis involves infestation of the external ear and/or middle ear. It is a rare clinical state that usually occurs in patients who have mental or physical disabilities. Although myiasis is a self-limiting disease, it can be associated with fatal complications like penetration within the central nervous system. We present a 87-year-old patient suffering from Alzheimer’s disease with aural myiasis and also discuss the clinical presentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 7 publications
(11 reference statements)
0
14
0
2
Order By: Relevance
“…It has been the most common causative agent for aural myiasis in Russia, Turkey and Israel (Hall and Wall 1995;Uzun et al 2004). The same fly was found responsible for aural myiasis in an 87-year-old bedridden female suffering from Alzheimer's disease from Turkey (Mengi et al 2014). Different studies have reported the occurrence of aural myiasis in humans (Curtis 1956;Keller and Keller 1970;Davies 1976;Sharan and Isser 1978;Varledzides et al 1981;El-Boulaqi et al 1983;El-Deeb et al 1988;El-Kadery and El-Begermy 1989;Fawzy 1991;Lee and Yong 1991;Magliulo et al 2000;Demirci et al 2006;Hatten et al 2010;Kaczmarczyk et al 2011).…”
Section: Aural Myiasismentioning
confidence: 89%
“…It has been the most common causative agent for aural myiasis in Russia, Turkey and Israel (Hall and Wall 1995;Uzun et al 2004). The same fly was found responsible for aural myiasis in an 87-year-old bedridden female suffering from Alzheimer's disease from Turkey (Mengi et al 2014). Different studies have reported the occurrence of aural myiasis in humans (Curtis 1956;Keller and Keller 1970;Davies 1976;Sharan and Isser 1978;Varledzides et al 1981;El-Boulaqi et al 1983;El-Deeb et al 1988;El-Kadery and El-Begermy 1989;Fawzy 1991;Lee and Yong 1991;Magliulo et al 2000;Demirci et al 2006;Hatten et al 2010;Kaczmarczyk et al 2011).…”
Section: Aural Myiasismentioning
confidence: 89%
“…Infection is more common in tropical locations with a warm and humid environment and manifestation commonly occurs in patients with poor personal hygiene, children, and mentally retarded adults [ 5 , 6 ]. Patients mostly present themselves with sensation of foreign substance in the ear, aural itching, pain, bleeding, tinnitus, hearing loss, and vertigo [ 7 - 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 Predisposing factors for myiasis in humans are low socioeconomic status, poor personal hygiene, mental retardation, child neglect, old age, and diabetes mellitus. 2,3 Myiasis can cause fatal complications, although it is a self-limiting disease since the eggs fully mature within 4 to 7 days after which the maggots leave their host. [2][3][4] Aural myiasis is the infestation of the external and/or middle ear.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Myiasis can cause fatal complications, although it is a self-limiting disease since the eggs fully mature within 4 to 7 days after which the maggots leave their host. [2][3][4] Aural myiasis is the infestation of the external and/or middle ear. 5 Flies lay eggs even during flight and are attracted by odoremanating from the ear, and chronic lesions, especially chronic suppurative otitis media, contribute to this.…”
Section: Introductionmentioning
confidence: 99%